PREGNANCIES IN WOMEN WITH COVID-19. CLINICAL CASES OF THE OUTCOME OF CHILDBIRTH - Юлия Валерьевна Васютинская; Данил Викторович Вебер; Василий Васильевич Жданов; Игорь Вадимович Пачгин; Ольга Борисовна Зарубина; Анастасия Александровна Подушко; Анна Васильевна Христова; Ольга Борисовна Карелина; Елена Владимировна Рудаева; Вадим Гельевич Мозес; Светлана Ивановна Елгина; Владимир Вячеславович Павленко (The Publishing House Medicine and Enlightenment, 2022)
The data available to date indicate that a new coronavirus infection can have an adverse effect on the course of pregnancy and may affect perinatal outcomes.